Gold Carbenoids: Lessons Learnt from a Transmetalation Approach - Seidel, Günter; Gabor, Barbara; Goddard, Richard; Heggen, Berit; Thiel, Walter; Fürstner, Alois (Angewandte Chemie International Edition, 2014)
Carbophilic catalysts that are based on AuI allow a host of different nucleophiles to be added across various π systems.1–3 Although many of these reactions are thought to proceed via gold carbenoids, the challenge to observe and characterize these putative intermediates has basically been unmet.4 The current mechanistic interpretation therefore largely relies on indirect evidence and computational data, some of which are subject to debate.5 In an attempt to fill this gap, we pursued a potential route to gold carbenoids by formal transmetalation of chromium or tungsten Fischer carbene complexes with [LAu]+. Whereas this transformation proceeds with exceptional ease as long as a stabilizing heteroelement is present on the carbene center, it stops half‐way in its absence. Rather unusual bimetallic arrays are formed, which allow the charge density to delocalize over several positions. The obvious difficulty of releasing an “unstabilized” gold carbenoid has potential mechanistic implications for the understanding of π‐acid catalysis in general. I do not want to be free! Whereas prototype Fischer‐type chromium carbene complexes transfer their organic ligand to gold with exceptional ease, chromium complexes devoid of the heteroelement substituent do not want to release unstabilized gold carbenoids of the type that is often invoked in mechanistic discussions of π‐acid catalysis. Instead, unusual bimetallic arrays are formed in which charge density gets delocalized over several positions.